Praktik pemulasaraan jenazah di Desa Sobo dalam perspektif pendidikan agama Islam - Pamungkas, Indra Ari; Subir, Muhammad Syuhada'; Fauzi, Haris (Idarah Tarbawiyah: Journal of Management in Islamic Education, 2026)
The preparation of the deceased is a collective obligation (fardhu kifayah) that embodies theological, social, and educational values in Islamic teachings. This study aims to examine the practice of preparing the deceased in Sobo Village and analyze it from the perspective of Islamic Religious Education (PAI). The approach used is descriptive qualitative, employing data collection techniques such as observation, in-depth interviews, and documentation. Informants were selected through purposive sampling, including religious leaders, community leaders, and residents directly involved. Data validity was ensured through triangulation techniques. The results indicate that funeral preparation practices in Sobo Village generally align with Islamic jurisprudence (fiqh) principles regarding the stages of washing, shrouding, performing the funeral prayer, and burial. The learning process that takes place is experiential learning based on community traditions. However, there are several challenges, namely the minimal use of personal protective equipment (PPE), a lack of participation from the younger generation, and limitations in the systematization of knowledge. This study concludes that there is a need for integration between formal and informal education, strengthening the training of the younger generation, and the internalization of modern health standards that are in harmony with the values of Islamic Sharia. Abstrak Pemulasaraan jenazah merupakan kewajiban kolektif (fardhu kifayah) yang mengandung nilai teologis, sosial, dan edukatif dalam ajaran Islam. Penelitian ini bertujuan untuk mengkaji praktik pemulasaraan jenazah di Desa Sobo dan menganalisisnya dalam perspektif Pendidikan Agama Islam (PAI). Pendekatan yang digunakan adalah kualitatif deskriptif dengan teknik pengumpulan data melalui observasi, wawancara mendalam, dan dokumentasi. Pemilihan informan dilakukan secara purposive yang meliputi tokoh agama, tokoh masyarakat, serta warga yang terlibat langsung. Keabsahan data dijamin melalui teknik triangulasi. Hasil penelitian menunjukkan bahwa praktik pemulasaraan jenazah di Desa Sobo secara umum telah sesuai dengan prinsip-prinsip fikih Islam dalam tahapan memandikan, mengafani, menshalatkan, dan menguburkan. Proses pembelajaran yang berlangsung bersifat experiential learning berbasis tradisi komunitas. Namun, terdapat beberapa tantangan, yaitu minimnya penerapan alat pelindung diri (APD), kurangnya partisipasi generasi muda, serta keterbatasan sistematisasi pengetahuan. Penelitian ini menyimpulkan bahwa diperlukan integrasi antara pendidikan formal dan informal, penguatan kaderisasi generasi muda, serta internalisasi standar kesehatan modern yang selaras dengan nilai-nilai syariat Islam.